On trans-para-Sasakian manifolds - Ozkan, Mustafa; Erken, Irem Kupeli; De, Uday Chand (Univ Nis, Fac Sci Math, 2024)
In this paper, we investigate the geometry of the trans-para-Sasakian manifolds. Finally, an example of a three-dimensional trans-para-Sasakian manifold is constructed to verify the results.
Keywords: Trans-para-Sasakian manifolds; Ricci semi-symmetric manifolds; almost paracontact manifolds; paracontact manifolds